Digital Transformation and Entrepreneurial Mindset: Unpacking the Performance of SMEs in Nigeria - Danjuma, Obiora Tanimola (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study investigates the impact of Digital Platform Capability (DPC) and Entrepreneurial Orientation (EO) on the performance of small and medium-sized enterprises (SMEs) in Nigeria, with EO also examined as a mediator between DPC and SMEs performance. Data were collected from 150 SME owners and managers in three major Nigerian cities — Lagos, Abuja, and Kano — through a structured questionnaire. Using structural equation modeling, the findings reveal that DPC has a significant positive effect on both EO and SMEs performance. EO also significantly enhances SMEs performance and partially mediates the relationship between DPC and performance. These results highlight the dual role of digital platforms: directly improving business outcomes and fostering entrepreneurial behaviors that further enhance performance. The study underscores the importance of integrating digital capabilities with entrepreneurial orientation to maximize the benefits of digitalization for SMEs. Practical and theoretical implications are discussed.